(untitled) (Praxis Educativa, 2021)
Theobjective of thisarticleis to reporttheresults of a doctoral researchcurrentlycompletedwhoseobjectiveis to knowthe causes whyuniversityacademics in Chile, havingretiredornotfromtheacademicwork, delaythebeginning of theretirementstage;specifically, theperceptionstheyhaveregardingtheirfuture are exposed. Theresearch of a mixednatureinvolves a quantitative and a qualitativephase. Theresults of thequalitativedeepeningphase are presented in thisarticle. Forthesepurposes, 21 academicsbetween 55 and 76 yearsbelonging to nine public and private universities in the country and working in nine differentcareershavebeeninterviewed. Theresults show thatChileanacademicswould be delayingthestart of theirretirementperiodmainlydue to vocational, economic, health and legal factors.